Mechanism of polyamine induced colistin resistance through electrostatic networks on bacterial outer membranes - Li, Jianguo (2021)
Naturally occurring linear polyamines are known to enable bacteria to be resistant to cationic membrane active peptides. To understand this protective mechanism, molecular dynamics simulations are employed to probe their effect on a model bacterial outer membrane. Being protonated at physiological pH, the amine groups of the polyamine engage in favorable electrostatic interactions with the negatively charged phosphate groups of the membrane. Additionally, the amine groups form large number of hydrogen bonds with the phosphate groups. At high concentrations, these hydrogen bonds and the electrostatic network can non-covalently crosslink the lipid A molecules, resulting in stabilization of the outer membrane against membrane active antibiotics such as colistin and polymyxin B. Moreover, large polyamine molecules (e.g., spermidine) have a stronger stabilization effect than small polyamine molecules (e.g., ethylene diamine). The atomistic insights provide useful guidance for the design of next generation membrane active amine-rich antibiotics, especially to tackle the growing threat of multi-drug resistance of Gram negative bacteria.